The Fragmentation of the Ethnic Segments in Plural Societies –the Macedonian Case - Bakiu, Qashif; Sela, Ylber (European Journal of Social Science Education and Research, 2022)
In cases where different parts of society live in geographical proximity, but in social aspect separated, the appearance of segmentation is one of the characteristics. Establishing the segments is done mainly on the ethnic grounds, but there are religious, linguistic, and racial based cases as well. Such a social phenomenon is present in Macedonia, wherein this phenomenon is more reflected in the relation between two major communities, the Macedonian and Albanian communities. If merely on social indicators researched so far, we can conclude that the ethnic communities are fragmented to a very high degree, that the same have no common ground, especially the one of political – party common ground. The previous conclusion is the presence of ethno-party pluralism. In this paperwork, in practical terms, our aim is to prove the high degree of fragmentation of ethnic segments in political action plan, respectively that of political party, as well as to determine the lines of expectations of the process flow, in view of the partisan multi-ethnic interaction or inaction. The measurement level of the fragmentation of segments is done by two sociological surveys (with approximately 1,000 respondents) specific to this case, for both ethnic communities, having involved the other ethnicities as well. Meanwhile, apart from other age groups, a special approach is made to the youngest age group, defining the two target groups of 18-25 and 25-30 years. Other reasons influencing the stagnation of partisan inter-ethnic cooperation have been part of this treatment as well.